Reproducibility of myocardial T1 and T2 relaxation time measurement using slice‐interleaved T1 and T2 mapping sequences. Issue 5 (4th April 2016) - Bellm, Steven; Basha, Tamer A.; Shah, Ravi V.; Murthy, Venkatesh L.; Liew, Charlene; Tang, Maxine; Ngo, Long H.; Manning, Warren J.; Nezafat, Reza
Abstract : Purpose: To assess measurement reproducibility and image quality of myocardial T1 and T2 maps using free‐breathing slice‐interleaved T1 and T2 mapping sequences at 1.5 Tesla (T). Materials and Methods: Eleven healthy subjects (33 ± 16 years; 6 males) underwent a slice‐interleaved T1 and T2 mapping test/retest cardiac MR study at 1.5T on 2 days. For each day, subjects were imaged in two sessions with removal out of the magnet and repositioning before the subsequent session. We studied measurement reproducibility as well as the required sample size for sufficient statistical power to detect a predefined change in T1 and T2 . In a separate prospective study, we assessed T1 and T2 map image quality in 241 patients (54 ± 15 years; 73 women) with known/suspected cardiovascular disease referred for clinical cardiac MR. A subjective quality score was used to assess a segment‐based image quality. Results: In the healthy cohort, the slice‐interleaved T1 measurements were highly reproducible, with global coefficients of variation (CVs) of 2.4% between subjects, 2.1% between days, and 1.7% between sessions. Slice‐interleaved T2 mapping sequences provided similar reproducibility with global CVs of 7.2% between subjects, 6.3% between days, and 5.0 between sessions. A lower variability resulted in a reduction of the required number of subjects to achieve a certain statistical power when compared with other T1 mapping sequences. In the subjective image quality assessment, >80% of myocardial segments had interpretable data. Conclusion: Slice‐interleaved T1 and T2 mapping sequences yield highly reproducible T1 and T2 measurements with >80% of interpretable myocardial segments. J. Magn. Reson. Imaging 2016;44:1159–1167.